Worship of the Banyan tree and Shiva linga - Temples of India Project Team (Jio Institute, 2024)
Worship of the banyan Tree and Shiva linga (aniconic representation of Shiva) by devotees in the month of Kartik (October-November) in the Chandrabhaga temple complex.